2020
DOI: 10.3126/njog.v15i1.29340
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of postmenopausal women of Kaski district

Abstract: Aim: To assess menopause specific quality of life of postmenopausal women. Method: This descriptive survey was carried out among postmenopausal women aged 40 to 60 years residing in a municipality of Kaski district of Nepal. Data was collected from 150 women meeting the criteria through face to face interview using a structured questionnaire consisting of socio-demographic items and Menopause-Specific Quality of Life (MENQOL) scale. Results: Respondents’ mean age and SD was 52.83±4.19 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
4
4
2
Order By: Relevance
“…[12][13][14] In the present study, the mean age of menopause was found as 47.18 (�6.16) years which is comparable to the findings of earlier studies conducted in India, Pakistan and Nepal that show a range between 46 and 49 years. 12,15,16 This finding corresponds to the finding for the age range of developing countries.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[12][13][14] In the present study, the mean age of menopause was found as 47.18 (�6.16) years which is comparable to the findings of earlier studies conducted in India, Pakistan and Nepal that show a range between 46 and 49 years. 12,15,16 This finding corresponds to the finding for the age range of developing countries.…”
Section: Discussionsupporting
confidence: 86%
“…The finding is comparable to the findings of a study conducted in Kaski district of Nepal. 16 In contrast to the finding, Sagdeo and Arora in a comparative study in rural and urban women showed the most common problem as joint and muscular symptoms followed by hot flushes and night sweats. 19 In another study conducted by Karmakar N et al, the most prevalent symptoms reported were feeling of anxiety and nervousness, feeling tired and decrease in stamina.…”
Section: Discussionmentioning
confidence: 75%
“…The menopausal symptoms are prevalent in our society as evidenced by the fact that all of the respondents have at least one of the menopausal symptoms. High prevalence of menopausal symptoms was also reported by the other studies from Nepal (9,11). The most common symptoms reported were from physical symptoms domain, present in all of the participants while the vasomotor symptoms were present in 47.5% of respondents with sweating and hot flushes as common symptoms.…”
Section: Discussionsupporting
confidence: 76%
“…The mean age of onset of menopause in the study was 47.14±4.38 years which falls under the normal range of women attaining menopause worldwide as well as the average age reported for Nepalese women (3,9). The age of menopause was however lower than 51.1 years, the median age for Asian women reported from a study conducted in seven Asian countries (10).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation